Design of Functional Bellyband for Pregnant Women (Journal of Fiber Bioengineering and Informatics, 2015)
This study has investigated the physical characteristics and needs of pregnant women to introduce a\rscientific and practical design of bellyband to satisfy pregnant women demand. Structure and material\rof supporting bellyband have been introduced in the study and its functional rationality also has been\rverified by many testers. Finally, the experiment result has been proved that the design of supporting\rbellyband has helped pregnant women to ease the burden of their waist efficiently and effectively after\ranalysed the result very carefully.
Keywords: Pregnant Women; Supporting Bellyband; Functionality; Comfort